Research Paper : Screening and identification of new sources of resistance to sheath blight in wild rice accessions - Bashyal, B. M.; Rawat, Kirti; Singh, Dhiraj; Krishnan, S. Gopala; Singh, A. K.; Singh, N. K.; Aggarwal, Rashmi (The Indian Journal of Genetics and Plant Breeding, 2017)
A total of 218 wild rice accessions including O. rufipogon and O. nivara were evaluated under artificial inoculation for resistance to sheath blight disease for two years under field conditions. The germplasm identified as resistant to sheath blight were further evaluated through artificial inoculation for an additional year under glass house conditions. Based on three years of testing, two Oryza rufipogon accessions, namely, IC336719 and IC336721 were identified as resistant to sheath blight disease. In vitro characterization of resistant genotypes revealed that the size of sheath blight lesion formation was small along with comparatively lesser number of infection cushions and penetration pegs as compared to the susceptible checks. The O. rufipogon accessions identified in the present study are very valuable genetic resource, which can be utilized in the development of introgression lines and mapping QTL(s) governing resistance to sheath blight of rice.